REVOLUSI MENTAL MELALUI PENERAPAN KEBIJAKAN GERAKAN MAGRIB MENGAJI DI KABUPATEN LEBAK - jumanah, jumanah; Badrussalam, Ujang (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
Maghrib Mengaji Community Movement or better known as GEMMAR Mengaji is a national program of the Ministry of Religion of the Republic of Indonesia which is launched in every Province and Regency / City in Indonesia(Revelation, 2018). Indonesian Muslims constitute the majority community where almost all Indonesian citizens are predominantly Muslim. According to the 2010 statistical data, Muslims in Indonesia totaled 207,176,162 people or 87.18% followed by Christianity with a percentage of 6.96%, in the next position, namely Catholicism with a percentage of 2.91%, Hinduism 1.69%, Buddhism. 0.72, and Khong hu chu 0.05%. Today people prefer to spend their time watching television than reading the Koran or other positive activities(Kristiawan, 2016). This also happens in Lebak Regency as an area which also has the characteristics of the majority being Islam. So that with the implementation of the perda, the magrib reciting movement can bring about mental changes in thinking, especially among children and adolescents for a better life. The method used in this research is a qualitative method. The results in this study indicate that the implementation of the maghrib recitation regional regulation is quite good if viewed from the communication dimension which shows the socialization carried out by the implementing agency, resources in the form of incentive support for reciting teachers, adequate facilities in the implementation of magrib recitation, and the number of teachers. sufficient recitation.